Effect of Oil Price on the Stock Market Return and Volatility in Six Major Oil Exporting Countries - Amin, Masoud Yousefi (2011)
This dissertation analyzes the dynamic relationship between oil price changes and stock market for the six main net oil exporting countries namely IRAN, RUSSIA, SAUDI ARABIA, NIGERIA, NORWAY and United Arab Emirates using weekly data from 16/1/2005–15/6/2010. The unrestricted multivariate Vector Autoregressions (VAR) model with 4 parameters (stock market return, oil domestic price changes, industrial production growth and world market return) is estimated as well as impulse response function and variance decomposition. The bivariate BEKK GARCH (1, 1) model is also used to show the impact of oil price volatility spillover on stock market volatility. The empirical results of the impact of oil price shocks on the stock market return indicate that in most oil exporting countries, oil price shocks have undeniable effect on the stock market variation in the same week or in two weeks. However, the strength of shocks response in the stock market of countries changes adversely by the pick in RUSSIA and the least in NIGERIA and NORWAY. The comparison between impacts of oil price shocks and world market return shocks on the stock market show that in four out of six countries world market shocks have much more influential role in stock market variation than oil price shocks. By exception of NORWAY it is found that most of oil exporters’ countries are much more sensitive to the shock by fall in oil price. However, empirical evidence is supported higher effective impact of surge shocks in NORWAY stock market return. Taking to the account different levels of reaction to the positive and negative oil price shocks the asymmetric impact of oil price shocks is completely apparent among most of countries. In the sub-sample of 2005 to 2010 stock market have experienced high volatility weeks. Experimental findings of BEKK GARCH (1, 1) in the oil exporter countries financial market indicates that there is some strong evidence on linkage of lag-leads effect of oil price variation on stock market return volatility in RUSSIA, NIGERIA, NORWAY and IRAN. It is also highlighted that oil price volatility of first lag can be better traced by the domestic volatility identifications of oil price change in comparison to the US dollar.